The Role of Digital Accounting Information Systems in Supporting Business Decision-Making - Andi Qarina; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of information technology has accelerated digital transformation across business functions, including accounting. This study aims to examine the role of Digital Accounting Information Systems (DAIS) in providing high-quality information and supporting business decision-making processes. The research employed a qualitative non-empirical approach using a literature review method. Secondary data were collected from scholarly journals, books, and academic publications related to digital accounting systems, information quality, and managerial decision-making. Data were analyzed through qualitative content analysis and thematic synthesis to identify recurring patterns and conceptual relationships within the literature. The findings indicate that DAIS enhances information quality by improving accuracy, timeliness, relevance, integration, and accessibility of financial information. These capabilities support operational, tactical, and strategic decision-making while contributing to organizational efficiency, performance evaluation, internal control, and strategic flexibility. The review also reveals several implementation challenges, including investment costs, technological readiness, human resource competencies, and cybersecurity concerns. The study concludes that DAIS functions not only as a financial reporting tool but also as a strategic organizational resource that strengthens decision quality and supports sustainable business performance in the digital era.